Demonizing the Jews : Luther and the Protestant church in Nazi Germany - Probst, Christopher J., 1969- (Indiana University Press, 2012)
The acquiescence of the German Protestant churches in Nazi oppression and murder of Jews is well documented. In this book, Christopher J. Probst demonstrates that a significant number of German theologians and clergy made use of the 16th-century writings by Martin Luther on Jews and Judaism to reinforce the racial antisemitism and religious anti-Judaism already present among Protestants. Focusing on key figures, Probst's study makes clear that a significant number of pastors, bishops, and theologians of varying theological and political persuasions employed Luther's texts with considerable effectiveness in campaigning for the creation of a "de-Judaized" form of Christianity. Probst shows that even the church most critical of Luther's anti-Jewish writings reaffirmed the antisemitic stereotyping that helped justify early Nazi measures against the Jews